2018
DOI: 10.24018/ejece.2018.2.5.27
|View full text |Cite
|
Sign up to set email alerts
|

Saving Energy by Replacing IM with BLDC Motor in Fan Application

Abstract: Electrical drives with single-phase and three-phase induction motors have been dominant in electromechanical energy conversion in industrial, residential and automotive applications. So far the using of induction motor in these sectors has been a good choice because of its reliability, long life, simple structure, stability, etc. Technological progress in magnetic material technology, power electronics, integrated circuits and microcontrollers have enabled alternative motor technologies such as brushless direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…The power consumption of BLDC ceiling fans is reduced to 20% at low speeds compared with AC induction ceiling fans [17]. Meanwhile, in another study, replacing induction motors with BLDC motors in fans reduced the power consumption of the fan by up to 35% [18]. Through the measurement of the power consumption of the DC ceiling fans developed locally and commercially available in the market it is found that BLDC ceiling fans also consume 35% less power than the conventional AC induction fans.…”
Section: Introductionmentioning
confidence: 99%
“…The power consumption of BLDC ceiling fans is reduced to 20% at low speeds compared with AC induction ceiling fans [17]. Meanwhile, in another study, replacing induction motors with BLDC motors in fans reduced the power consumption of the fan by up to 35% [18]. Through the measurement of the power consumption of the DC ceiling fans developed locally and commercially available in the market it is found that BLDC ceiling fans also consume 35% less power than the conventional AC induction fans.…”
Section: Introductionmentioning
confidence: 99%
“…The modern trend of DC-inverter-based air conditioning systems is also DC in nature, providing energy savings as compared to conventional air conditioning systems [15]. The brushless DC (BLDC) motor is replacing the conventional induction motor in appliances with an added advantage of energy savings [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the machine should be manufactured with auxiliary winding or shaded pole to prevent this situation in single-phase induction motors [1][2][3]. Shaded pole induction motors are preferred, especially in low-power applications, due to their simple structure, low cost, and direct operation from a single-phase source [4,5]. However, these motors cannot compete with three-phase motors, especially in industrial applications that require high power.…”
Section: Introductionmentioning
confidence: 99%